MAQASID SYARIAH DAN PENGARUH PELARANGAN BUNGA DALAM PEREKONOMIAN NASIONAL - Muhammad Baiquni Syihab (Kopertais Wilayah III Yogyakarta, 2022)
Abstract Bank interest as stated by MUI is usury, and usury is unlawful. However, bank interest cannot be released from the economic system because it functions as a financial instrument that regulates the money supply. Without interest, the banking operational system cannot run. Without service fees from the central bank, the banking operational system (both conventional and sharia) cannot function as it should. Maqasid sharia is the purpose and wisdom of establishing a law given by the Khaliq (Allah), then of course the forbidden law on the practice of muamalah flowering (usury) has a purpose and wisdom. And as revealed in the Qur'an that the prohibition of usury is intended so that humans are not wrongdoers who wronged and no one was wronged in terms of property. In this discussion we reveal, that the practice of bank interest is the main cause of inflation. Inflation itself means a decrease in the value of money, and not an increase in the price of goods. That is, it is possible that among the community there is absolutely no practice of usury, but still it has a bad impact, exposed to dirty splashes of usury practice. Namely, the wealth of money that he has has decreased in value due to inflation. Keyword: Interest, Riba, Maqasid Sharia